2006
DOI: 10.1111/j.1365-2788.2006.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being, involvement in paid work and division of child‐care in parents of children with intellectual disabilities in Sweden

Abstract: Families with children with ID differ from control families in that the parents are less involved in paid work and have lower levels of well-being. A positive relation between involvement in paid work and well-being was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 14 publications
5
107
0
8
Order By: Relevance
“…Os pais são menos afetados e uma razão, para isso, é a tendência de serem menos envolvidos no cuidado da criança do que as mães e mais envolvidos em outros domínios da vida, como o trabalho 26 .…”
Section: Discussionunclassified
“…Os pais são menos afetados e uma razão, para isso, é a tendência de serem menos envolvidos no cuidado da criança do que as mães e mais envolvidos em outros domínios da vida, como o trabalho 26 .…”
Section: Discussionunclassified
“…The main reason for needing financial assistance is unemployment (National Board of Health and Welfare 2012b). Parents of children with ID in Sweden have reported that they reduce their hours of paid work to be able to take care of their children properly (Olsson and Hwang 2006).…”
Section: Services Received Because Of Social Problems In Relation To mentioning
confidence: 99%
“…Internasjonale studier av yrkesdeltakelsen blant foreldre med barn med spesielle behov viser at det er mindre sannsynlighet for at kvinner er ute i arbeidslivet, og at forekomsten av deltidsarbeid er høyere sammenlignet med kvinner med barn uten spesielle behov (Olsson & Hwang 2006;Porterfield 2002;Seltzer, Greenberg, Floyd, Pettee & Hong 2001). En ny norsk studie viser imidlertid at det ikke er mindre sannsynlig at mødre til barn med spesielle behov er i arbeid, sammenlignet med mødre generelt.…”
Section: Begrenset Kunnskap Om Familienes Handlingsmuligheterunclassified